2016
DOI: 10.1016/j.freeradbiomed.2016.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates oxidative stress in mitochondrial Complex I deficiency: Involvement of SIRT3

Abstract: The pathophysiological mechanisms underlying Complex I (CI) deficiencies are understood only partially which severely limits the treatment of this common, devastating, mitochondrial disorder. Recently, we have shown that resveratrol (RSV), a natural polyphenol, has beneficial effects on CI deficiency of nuclear origin. Here, we demonstrate that RSV is able to correct the biochemical defect in oxygen consumption in five of thirteen CI-deficient patient cell lines. Other beneficial effects of RSV include a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
3
33
0
1
Order By: Relevance
“…Oxidative stress and inflammatory markers also have been associated with depression and nicotine dependence (35). A study by Mathieu et al indicated that resveratrol attenuated oxidative stress in mitochondrial complex I deficiency through regulation of the sirtuin 3 signaling pathway (36). In the present study, it was observed that resveratrol treatment attenuated oxidative stress in hippocampal neuron cells, which may have contributed to the recovery in depressive disorder.…”
Section: Discussionsupporting
confidence: 58%
“…Oxidative stress and inflammatory markers also have been associated with depression and nicotine dependence (35). A study by Mathieu et al indicated that resveratrol attenuated oxidative stress in mitochondrial complex I deficiency through regulation of the sirtuin 3 signaling pathway (36). In the present study, it was observed that resveratrol treatment attenuated oxidative stress in hippocampal neuron cells, which may have contributed to the recovery in depressive disorder.…”
Section: Discussionsupporting
confidence: 58%
“…Compound 1 also attenuates oxidative stress in fibroblasts from patients with Complex I deficiency by increasing SOD2 in a SIRT3-dependent manner. 83 Human clinical trials using 1 demonstrated improved lipid profiles, antioxidant defenses, and vascular reactivity in diabetic and obese subjects; 8489 however, there are conflicting data regarding the effect of 1 on insulin sensitivity, 84, 88, 90 and 1 had no effect in non-obese subjects. 91 …”
Section: Natural Productsmentioning
confidence: 99%
“…Previous reports showed that resveratrol reduced oxidative stress under SIRT3 control in mitochondrial complex I deficiency. 46 In human vascular endothelial cells, resveratrol also maintained mitochondrial reactive oxygen species homeostasis through activation of the SIRT3 signaling pathway. 47 An interesting and novel finding of our study was that the effect of resveratrol on SIRT4 gene expression increased 15-fold when compared to control, and protein expression highly increased in the zebrafish retina.…”
Section: Discussionmentioning
confidence: 99%